Budgeting in Finland - Blöndal, Jón R.. (OECD Publishing, 2003)
The budget is the most fundamental and important document of governments. It is the key economic document in that it allocates a significant share of a nation's gross domestic product, over half in some OECD member countries. It is the key program policy document in that governments establish their policy priorities in concrete terms in the budget through the allocation of funding. It is the key management document in that the basic operational aspects of government ministries and agencies are established in the context of the budget. Furthermore, the budget provides the basic architecture for overall decision-making and accountability in government. This architectural design has a significant impact on overall government performance